Is it night or day? - Chapman, Fern Schumer (New York : Farrar, Straus, Giroux, 2010)
Twelve-year-old Edith is sent from her home in Germany in 1938 to live with her aunt and uncle in Chicago, Illinois, and escape Nazi persecution, but as she struggles to assimilate into American society, Edith worries about her parents and mourns the loss of everything she has known. Includes information on an American rescue operation that saved twelve hundred Jewish children between 1934 and 1945.
Booklist starred
School Library Journal
Wilson's Junior High School
Booklist starred, February 2010
Horn Book, October 2010
Kirkus Review, February 2010
Keywords: Holocaust, Jewish (1939-1945) -- Juvenile fiction; Jewish refugees -- Juvenile fiction; Jews -- Germany -- Juvenile fiction; Jews -- United States -- Juvenile fiction; World War, 1939-1945 -- Jews -- Rescue -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Fiction; Jewish refugees -- Fiction; Jews -- Germany -- Fiction; Jews -- United States -- Fiction; World War, 1939-1945 -- Jews -- Rescue -- Fiction; Historical fiction; Holocaust, 1939-1945 -- Fiction; Jewish refugees -- Fiction; Jews -- Germany -- Fiction; Jews -- United States -- Fiction; World War, 1939-1945 -- Fiction; Chicago (Ill.) -- History -- 20th century -- Juvenile fiction; Chicago (Ill.) -- History -- 20th century -- Fiction; Chicago (Ill.) -- History -- Fiction; Historical fiction